2003
DOI: 10.1515/advg.2003.2003.s1.206
|View full text |Cite
|
Sign up to set email alerts
|

Caps on Hermitian varieties and maximal curves

Abstract: A lower bound for the size of a complete cap of the polar space H(n, q 2 ) associated to the non-degenerate Hermitian variety U n is given; this turns out to be sharp for even q when n = 3. Also, a family of caps of H(n, q 2 ) is constructed from F q 2 -maximal curves. Such caps are complete for q even, but not necessarily for q odd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Unfortunately not much is known about large maximal partial spreads of Q(4, q), and the largest known such partial spread is still much smaller than the theoretical bound q 2 − q + 1, q odd. Finally it is interesting to note that in [9] Hirschfeld and Korchmáros construct maximal partial spreads of Q(5, q) (in fact they construct maximal partial ovoids of H(3, q 2 )) from GF(q 2 )-maximal curves for even q. However, their examples have size q 2 + 1 + 2gq, where g is the genus of the curve used, which is also still much larger then our obtained lower bound (except for the trivial case of rational algebraic curves which have genus 0 and yield maximal partial ovoids of size q 2 + 1).…”
Section: Theorem 46 ([11])mentioning
confidence: 98%
“…Unfortunately not much is known about large maximal partial spreads of Q(4, q), and the largest known such partial spread is still much smaller than the theoretical bound q 2 − q + 1, q odd. Finally it is interesting to note that in [9] Hirschfeld and Korchmáros construct maximal partial spreads of Q(5, q) (in fact they construct maximal partial ovoids of H(3, q 2 )) from GF(q 2 )-maximal curves for even q. However, their examples have size q 2 + 1 + 2gq, where g is the genus of the curve used, which is also still much larger then our obtained lower bound (except for the trivial case of rational algebraic curves which have genus 0 and yield maximal partial ovoids of size q 2 + 1).…”
Section: Theorem 46 ([11])mentioning
confidence: 98%
“…Hirschfeld and Korchmáros [10], proved that a maximal partial ovoid of H (n, q 2 ) has at least q 2 +1 points. They showed that this lower bound is sharp for n = 3 and even q. Aguglia, Ebert and Luyckx [1] dealt with small partial ovoids in H (3, q 2 ).…”
Section: Introductionmentioning
confidence: 99%